Sports media and the phenomenon of violence - maiza, mebarek; Ben Tayeb, Fatiha (sports creativity, 2025)
Various media and communication outlets capture our attention and almost besiege us everywhere we go, and at all times, as we have become exposed to the content of what we see, hear, or read daily in these media. Hence our intervention to study these contents to understand their effects and results on the audience, as there is no issue that warrants the attention of researchers as much as the issue of sports violence. Numerous studies have confirmed the role of various sports media in developing violent and aggressive behavior among their consumers when these media are exploited negatively without regard for controls and legal frameworks. Instead of these media seeking to contribute to sports socialization and working to spread sports awareness, and informing the public of the importance of sports in the psychological, social and mental integration of the individual, and introducing its laws and rules, and making its practice appealing to all members of society, and spreading its noble values, including sportsmanship, they become a means that contributes to developing and instilling violent and aggressive behavior in their consumers through what they broadcast in terms of exciting scenes, and what they focus on in the mistakes committed in sports practice, and provocative statements, and broadcasting disputes, and playing on emotions and other means of inciting violence and spreading values ​​of aggression among individuals.